Effects of post-exercise infrared sauna on training adaptations in team-sport athletes - Zhang, Tianyu (2023)
The aim of this study was to investigate the effects of post-exercise infrared sauna (IRS) on chronic training adaptations regarding physical performance, skeletal muscles, cardiovascular function, and haematological biomarkers in team-sport athletes. 23 female team-sport players were volunteered to participate and assigned to two groups to undertake a 6-week strength and power training programme with utilizing IRS recovery (IRS; n = 11) or without recovery implementation (CON; n = 12). The training program consisted of two or three complex resistance training sessions per week, with a 10-minute recovery period following each session. Before and after the 6-week training intervention, 20 m maximal sprint, maximal countermovement-jump, squat jump, and isometric leg press tests were performed to evaluate the adaptations in explosive physical performance. To assess the adaptations in skeletal muscle, body composition, cross-sectional area (CSA) and pennation angle of the vastus lateralis muscle were measured. Venous blood samples were collected pre and post-training intervention to analyse haematological parameters including red blood cells, haematocrit, and haemoglobin concentration. Significant increases were found in isometric leg press performance, whole-body fat-free mass (FFM), leg FFM and CSA following 6-week strength and power training (P < 0.05). No significant effect of utilizing IRS (time*group) has been indicated in all variables compared to using passive recovery (P > 0.05). It concludes that IRS as a recovery strategy does not have a detrimental impact on adaptations to strength and power training in team sport athletes. Moreover, it could be considered a favourable recovery strategy when frequent and long-term utilization is required, as previous evidence has indicated the benefits of IRS in acute recovery.